2019
DOI: 10.1016/j.jff.2019.04.046
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of yeasts isolated from traditional kefir grains for potential probiotic properties

Abstract: Kefir is a mixed fermented product with numerous attributed health benefits due to presence of a complex culture composed of bacteria and yeasts in an exopolysaccharide matrix. This work aimed at isolating and identifying culturable yeast species from two types of traditional kefir grains and establishing some potential probiotic properties including survival in the gastrointestinal tract, auto-aggregation, hydrophobicity and hydrolytic enzymes production. All the isolates showed good survival rates in simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
54
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 42 publications
8
54
0
4
Order By: Relevance
“…The cell hydrophobic and autoaggregation properties in the intestinal epithelial cells are considered as a probiotic criterion. The S. boulardii showed a good hydrophobic affinity and autoaggregation ability increases over time, which matches the previous study result (19,43).…”
Section: In-vivo Antidiarrheal Activities For Safety Evaluationsupporting
confidence: 91%
See 1 more Smart Citation
“…The cell hydrophobic and autoaggregation properties in the intestinal epithelial cells are considered as a probiotic criterion. The S. boulardii showed a good hydrophobic affinity and autoaggregation ability increases over time, which matches the previous study result (19,43).…”
Section: In-vivo Antidiarrheal Activities For Safety Evaluationsupporting
confidence: 91%
“…According to the result of the test (Figure 2D), the isolate was growing up to 8.0% NaCl concentration, but there was a rapid decrease in growth after 3.0% NaCl concentration (25). Simulated gastrointestinal juice tolerance is considered one of the major criteria for probiotics, which is a primary barrier against most ingested microorganisms (19,43). The current results thus revealed that the S. boulardii strain exhibited strong resistance to gastric juice (Figure 3) in pH 3.0 and almost 80% of cells successfully survived, with some previous study data strongly supporting the results (5,9,18).…”
Section: In-vivo Antidiarrheal Activities For Safety Evaluationmentioning
confidence: 99%
“…Adhesion of bacteria onto yeast cells was performed as previously described [46], with some modification. Briefly, the cultured yeast and ETEC K88 in suspensions was harvested by centrifugation at 8000 rpm/min for 10 min, respectively.…”
Section: Inhibition Of Bacterial Adhesionmentioning
confidence: 99%
“…Cell surface hydrophobicity is defined as a nonspecific interaction in adhesion between probiotic microorganisms onto GIT epithelial cells, where they may provide prophylactic and therapeutic benefits [ 20 ]. Colonization in the intestinal epithelial cell wall and mucosal surfaces can prevent pathogenic bacteria adhesion and inflammatory reactions [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Auto-aggregation is defined as aggregation among yeast cells to form flocs and colonize the intestinal environment of the host when the cells approach harmful conditions [ 20 , 23 ]. Probiotic microorganisms should be associated with higher auto-aggregation than pathogenic microorganisms [ 22 ], specifically Strep.…”
Section: Discussionmentioning
confidence: 99%